Engagement at Scale: Experimental Evidence on Interactivity and Purchase Behavior in Indonesia’s Live Commerce Ecosystem - Hanifah, Anisah Mutiara Zahra; Marthalia, Lia; Sapri (Indonesian Scientific Publication, 2024)
This study investigates how interactivity influences consumer purchase decisions in live commerce, focusing on short video platforms in Indonesia. As digital retail rapidly expands across Southeast Asia, live commerce particularly on platforms like TikTok Shop by Tokopedia has become a dominant format for real time engagement and conversion. The objective of this research is to provide empirical evidence on the causal effects of interactivity during live shopping sessions on key performance indicators such as trust, click through rates, and paid orders. Using a randomized field experiment design, the study categorizes live sessions into three treatment groups representing different levels of interactivity (low, moderate, high). Quantitative data were collected from 90 sessions hosted by certified sellers, supplemented by post session viewer surveys. Key metrics include chat frequency, response time, Q&A participation, and viewer trust scores. Analytical techniques include regression models and mediation analysis. Results show that higher interactivity significantly enhances engagement and drives stronger outcomes at each stage of the purchase funnel. Paid order rates increased from 1.2% in low interactivity sessions to 3.6% in high interactivity sessions. Trust was identified as a statistically significant mediator between interactivity and purchase behavior, reinforcing existing digital commerce theories such as the Stimulus Organism Response (S O R) model. These findings have critical implications for platform developers, marketers, and policymakers. Optimizing live commerce features to encourage real time interaction can improve trust and conversion outcomes, particularly in culturally collectivist and regulatory sensitive markets like Indonesia. The research highlights the need for adaptive platform design and regulatory foresight to balance innovation with compliance.